Numeric taxonomy approaches for lytic evaluation of Salmonella specific bacteriophages - Amorim, Lara R.P. (2011)
This study explored the lytic ability of bacteriophages as a future tool for reducing the Salmonella spp. loads in food animals. It investigated (a) the concept of a phage cocktail resulting from an exploratory analysis of the 13 phages which were examined, and (b) the possibility of using them in phage typing techniques for a broad range of serotypes. By using the conventional plaque assay method and cluster analysis, it was possible to select the 2/2, N5, 2a, 135KP and 120 phages, as potential elements of a cocktail as a means of efficiently eliminating the greatest number of several types of Salmonella. The 2/2 and N5 phages were also the most efficacious infective elements against the Typhimurium and Enteritidis serovars, respectively.